SOME ASPECTS OF WEANING — USE OF NEW MILK-BASED INDUSTRIALLY PROCESSED CEREAL PRODUCTS - E.V. Trofimenko (Вопросы современной педиатрии)
Due to National Program of Infant Nutrition in Russian Federation Optimization publication in 2010 and new infant nutrition products’ appearance, need improvement of knowledge in this field rises for many doctors. The article is devoted to such aspects of weaning as smooth transition from liquid nutrition to solid, choice of first weaning product, consideration of individual development features, importance of adapted products’ use. Introduction of weaning food to babies with difficulties in transition to solid products is viewed. Use of new milk-based cereal products — Vallings as well-balanced, nourishing food, allowing weaning following an individual scheme and also as a dietetic food is discussed.Key-words: babies of first year of life, nutrition, weaning, milk-based cereal products, Vallings.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):78-84)